Search for alternative magnetic tunnel junctions based on all-Heusler stacks - Sanvito, Stefano; Rotjanapittayakul, Worasak; Prasongkit, Jariyanee; Rungger, Ivan; Pijitrojana, Wanchai; Archer, Thomas (My University, 2018)
By imposing the constraints of structural compatibility, stability, and a large tunneling magneto-resistance, we have identified the Fe3Al/BiF3/Fe3Al stack as a possible alternative to the well-established FeCoB/MgO/FeCoB in the search for a novel materials platform for high-performance magnetic tunnel junctions. Various geometries of the Fe3Al/BiF3/Fe3Al structure have been analyzed, demonstrating that a barrier of less than 2 nm yields a tunneling magneto-resistance in excess of 25 000% at low bias, without the need for the electrodes to be half-metallic. Importantly, the presence of a significant spin gap in Fe3Al for states with Δ1 symmetry along the stack direction makes the TMR very resilient to high voltages.
PUBLISHED
Keywords: Structural compatibility; Spintronics; Heusler alloy; Tunnel junctions; Density functional theory